Can Rumex madaio (Polygonaceae) be threatened by natural hybridization with an invasive species in Japan. Issue 5 (3rd March 2022) - Uemura, Ryudo; Asakawa, Akira; Fujii, Shinji; Matsuo, Ayumi; Suyama, Yoshihisa; Maki, Masayuki
Abstract : Natural hybridization between the native species Rumex madaio endemic to Japan and the congeneric invasive species R. obtusifolius, which frequently co‐occurs with R. madaio, was examined by molecular identification. At low frequencies, interspecific hybrids between the two species were confirmed using restriction fragment length polymorphism analyses of the internal transcribed spacer region of ribosomal DNA. Whereas these two species can hybridize because their flowering periods overlapped to some extent, the extremely low fertility of R. madaio caused by unknown genetic factors seemed to prevent extensive hybridization between these species. Population genetic analyses based on single nucleotide polymorphisms showed that there was a distinct population genetic structure in R. madaio, suggesting that local populations should be treated separately for genetic conservation of the species.